Generation of functional liver organoids on combining hepatocytes and cholangiocytes with hepatobiliary connections ex vivo - Naoki Tanimizu (Nature Portfolio, 2021)
Combining mouse hepatocyte progenitors and cholangiocytes ex vivo, the authors form an organoid that can drain bile ex vivo and transport metabolites, as in the liver.